A Methodology to Analyze Significant Energy Uses and Energy Consumption for Improving Energy Performance in Higher Education Buildings - Diaz, Mauricio Chamorro; Viveros Mira, Miguel; Quispe, Enrique C.; Castrillón, Rosaura; Lasso, Ana; Vidal, Juan R. (International Journal of Energy Economics and Policy, 2023)
This paper introduces a methodology to conduct an energy assessment at a Higher Education Institution (HEI) based on the international standard ISO 50001. This methodology was applied at the Universidad Autónoma de Occidente (UAO) in Cali, Colombia, to develop energy consumption baselines for each building and the air conditioning system of the main building based on the establishment of relevant variables affecting the energy consumption of each Significant Energy Uses (SEUs). The energy assessment allows us to determine energy performance improvement opportunities. This study case identified that energy consumption could be reduced by 14,2% by applying actions on the campus lighting, office equipment, and air conditioning system. This study provides guidance and guidelines for conducting an energy assessment at a university campus, with restrictions on measuring energy consumption. It provides insights for other universities implementing an Energy Management System and the government for conducting public energy policies.